SeDeM tool-driven full factorial design for osmotic drug delivery of tramadol HCl: Formulation development, physicochemical evaluation, and in-silico PBPK modeling for predictive pharmacokinetic evaluation using GastroPlus™ - Saleem, Muhammad Talha; Shoaib, Muhammad Harris; Yousuf, Rabia Ismail; Ahmed, Farrukh Rafiq; Ahmed, Kamran; Siddiqui, Fahad; Mahmood, Zafar Alam; Sikandar, Muhammad; Imtiaz, Muhammad Suleman (Frontiers in Pharmacology, 2022)
The study based on using SeDeM expert system for developing controlled-release tramadol HCl osmotic tablets and its in-silico PBPK modeling for in-vivo pharmacokinetic evaluation. A new QbD based approach in developing SeDEM-driven full factorial osmotic drug delivery. A 24 Full-factorial design was used to make the trial formulations of tramadol HCl osmotic tablets. The preformulation characteristics of formulations (F1-F16) were determined by applying SeDeM Expert Tool. The formulation was optimized followed by in-vivo predictive pharmacokinetic assessment using PBPK ‘ACAT’ model of GastroPlusTM. The FTIR results showed no interaction among the ingredients. The index of good compressibility (ICG) values of all trial formulation blends were ≥5, suggesting direct compression as the best-suited method. F3 and F4 were optimized based on drug release control for up to 16 hours with a zero-order kinetic release (r2= 0.992 and 0.994). The SEM images confirmed micropores formation on the surface of the osmotic tablet after complete drug release. F3 and F4 were also stable (shelf life 29.41 and 23.46 months). The in-vivo simulation of pharmacokinetics by the PBPK in-silico model revealed excellent relative bioavailability of F3 and F4 with reference to tramadol HCl 50 mg IR formulations. The SeDeM expert tool was best utilized to evaluate the compression characteristics of selected formulation excipients and their blends for direct compression method in designing once-daily osmotically controlled-release tramadol HCl tablets. The in-silico GastroPlusTM PBPK modeling provided a thorough pharmacokinetic assessment of the optimized formulation as an alternative to tramadol HCl in-vivo studies.